PERTANGGUNGJAWABAN PIDANA PELANGGARAN HAK CIPTA LAGU DAN MUSIK TERHADAP SUBJEK HUKUM TINDAK PIDANA KORPORASI - Tatok Sudjiarto (Fakultas Hukum Universitas Kristen Indonesia, 2022)
Flows of globalization are increasing rapidly and developments of information technology are increasingly stimulating the acceleration of economic dynamics. It takes personal co-operation to create a group collaboration for economic gain. The group is a group of businesses that do not have legal entities, as well businesses that already have incorporated entities called corporations. Combining personal persons into a corporation will increase the strength of the existence of a corporation as a legal subject in the economic realm. A Subject of law (tumjuris subject) is anything that can be a supporter of rights and obligations. There is two subject of laws. the first subject is human (natuurlijke person) and the second is legal entities (rechts person). Corporate position as an economic power outside the state. It creating corporations tend to take control or monopolize all economic system without control from the government. These conditions generate corporations' activities can abuse the public interest that known as corporate crime. Corporate crime is committed to benefiting the company's business, this type of crime is part of white collar crime. This crime also pan of violation of economic rights of creator and owner rights related to Copyrights in the field of songs and/or music. Ideally, the existence of corporations in the field of economy is aimed to increase the economic growth of a country, then, a country can improve people's welfare. However, there are some corporations that violate the principle by committing a crime.